Coronary artery bypass grafting vs. drug-eluting stent implantation in patients with end-stage renal disease requiring dialysis - Zhi Wang; Yanjun Gong; Fangfang Fan; Fan Yang; Lin Qiu; Tao Hong; Yong Huo (Renal Failure, 2020)
Objectives To evaluate the optimal revascularization strategy for patients with coronary artery disease (CAD) and end stage renal disease (ESRD) in the drug-eluting stent (DES) era. Methods One hundred and twelve patients with ESRD treated with coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) were enrolled from 2007 to 2017. All patients were dialysis-dependent, of which 26 received CABG and 86 underwent PCI. The primary endpoint was all-cause mortality. Secondary endpoints were major adverse cardiovascular events including myocardial infarction, stroke, repeat revascularization, and death. Results The CABG group had a higher prevalence of left main CAD (57.7% vs. 11.6%, p < .01) compared with PCI group. The short-term (within 30 days after the procedure) risk of death was higher in CABG group compared with PCI group (15.4% vs. 1.2%, p < .05). The two groups exhibited similar rate of primary endpoints (50.0% vs. 40.7%, p = .37) and secondary endpoints (65.4% vs. 60.5%, p = .97) in long-term observation. Multivariate Cox regression showed that patients older than 65 or underwent peritoneal dialysis (PD) had significant higher rate of mortality than those under 65 (HR 2.85; 95% CI 1.20–6.85; p < .05) or underwent hemodialysis (HD) (HR 6.69; 95% CI 2.35–19.05; p < .01). Conclusions Among patients with CAD and dialysis-dependent chronic kidney disease (CKD), treatment with CABG or PCI with DES exhibited similar long-term outcomes. However, CABG was associated with higher short-term risk of death. Higher mortality was revealed in patients over 65 years and underwent PD.